56.5: Pupil Swim Suppression in Augmented Reality (AR) Waveguide Combiner. (26th August 2021) - Zhao, Xin; Liu, Feng; Zheng, Yu
Abstract : Pupil Swim refers to change in extent of distortion when human eye moves in exit pupil of near eye display. Though this artifact is rarely discussed in normal metrics of augmented combiner, it deteriorates the long‐time viewing experience of AR headsets. Previously, this phenomenon was noticeable to public in virtual reality (VR) optics with large field of view.[3] We recently take a survey and find similar occurrence in AR products, especially in geometric waveguide with large FOV and small F/#. In this work, we first give a phenomenal description of this issue and research on the optical aberrations creating this artifact. To address pupil swim, a practical design methodology was proposed based on a comprehensive discussion inclusive of the interaction of human vision and project virtual image. Future directions like using catoptric design were proposed to further suppress the pupil swim and improve the visual comfort of near eye display.